Constitutive model of disordered grid interpenetrating structure of flexible microporous metal rubber. (1st June 2021) - Ren, Zhiying; Shen, Liangliang; Bai, Hongbai; Pan, Ling; Zhong, Shuncong
Graphical abstract: Highlights: A micro spring element with adaptive deformation (MSEAD) is constructed to characterize the actual load of the micro-elements of the turns in the space randomly distributed. The spatial distribution law and friction motion form of micro-turns in FMR-MR are deeply explored and introduced as an important parameter in the constitutive relation. With the concept of combined probability distribution (CPD), a constitutive model based on FMR microscopic and macroscopic parameters is constructed to reflect the disordered grid interpenetrating structure (DGIS) of materials. Abstract: In this study, the disordered grid interpenetrating structure (DGIS) of wire turns in flexible microporous metal rubber (FMP-MR) for vibration and noise reduction is investigated, and an effective constitutive model is developed to dynamically capture the nonlinear mechanical behavior of FMP-MR. In this model, a micro spring element with adaptive deformation (MSEAD) model with random spatial distribution is employed, based on the phenomena of irregular overlapping and interlacing of material turns. The spatial distribution of micro springs and the evolution of the contact area morphology in FMP-MR are taken into consideration and introduced as key variables in model development. The concept of combined probability distribution (CPD) of micro spring pairs between wire turns in FMP-MR is proposed to characterize the random combination mode of material turns. Eventually, based on the micro-patterns of wire turns in FMP-MR, a constitutive model including macroscopic parameters, such as shape, density, wire diameter, helix pitch, and wire elastic modulus, and microstructure parameters, such as spatial distribution of wire turns, contact shape, and friction coefficient is developed for the first time. By analyzing and discussing the fitting degree of quasi-static compression experimental results and the model constitutive curves, the validity of the proposed constitutive model is quantitatively confirmed by residual analysis. According to the results, the FMP-MR constitutive model based on DGIS can effectively reflect the nonlinear mechanical behavior and complex micro-contact friction phenomena of the material.